Pola Tidur yang Buruk Meningkatkan Risiko Hipertensi - Santi Martini; Shofa Roshifanni; Fanni Marzela (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Poor sleep patterns of sleep disturbances, poor sleep quality, and short sleep duration may increase the riskof hypertension. Hypertension itself is now a disease that occupies a high position that is often experienced by thecommunity. The purpose of this study was to determine the relationship of poor sleep patterns behavior increasesthe risk of hypertension. This research was an observational research that is analytic with case control design.The sample in this study amounted to 76 people consisting of patients with hypertension and non hypertensionpatients in Public Poly, Primary Haelth Care Tanah Kalikedinding Surabaya. The sampling technique was doneusing simple random sampling. The result of the research using logistic regression test showed (p 0,000; OR 9,022)that sleeping pattern has the greatest influence to the happening of hypertension compared to age and gender. Thestrength of the influence of sleep patterns of respondents showed that respondents who had a good pattern had a9.022 times greater risk of not having hypertension than those who had poor sleep patterns. Poor sleep patternsinclude sleep disturbances, poor sleep quality, and short sleep duration. Recommendations given to respondentswho have bad sleep patterns should improve sleep patterns with a healthy lifestyle that is sleeping as needed andkeep the mind so as not to experience pressure because of excessive stress.